Effect of torsional angle on the fretting wear behavior and fracture failure mechanism of steel wires with spiral contact structure - Chunming Xu; Yuxing Peng; Kaituo Fang; Tao Jiang; Yanfeng Wang; Lei Yuan (Journal of Materials Research and Technology)
The fretting wear of steel wire will reduce the service life of wire rope and severely threaten the safety of mine hoisting. To investigate the influence of torsion on the fretting wear behavior of steel wire, the fretting wear tests of steel wires with spiral contact structure under the action of tensile-torsional coupling forces were conducted, and the fatigue fracture failure mechanism was revealed. The result indicates that the CoF increases with increasing torsional angle. As the cycles increase, the sliding distance between the wires decreases, while the adhesion increases. The fretting area gradually transitions from gross sliding status to partial sliding status. The sliding distance and energy loss between the wires increase with increasing torsional angle. The wear depth and coefficient increase with increasing torsional angle, and the wear level of peak contact structure is more serious than that of valley contact structure. The primary wear mechanisms of steel wire are abrasive wear, adhesive wear and fatigue wear. The fatigue fractograph of steel wire is obviously divided into fatigue source zone, crack growth zone and final fracture zone. Abundant secondary cracks and dimples exist in the final fracture zone, and the fatigue fracture failure mechanism is mainly ductile fracture.